2017
DOI: 10.1002/bjs.10552
|View full text |Cite
|
Sign up to set email alerts
|

Safety, productivity and predicted contribution of a surgical task-sharing programme in Sierra Leone

Abstract: BackgroundSurgical task‐sharing may be central to expanding the provision of surgical care in low‐resource settings. The aims of this paper were to describe the set‐up of a new surgical task‐sharing training programme for associate clinicians and junior doctors in Sierra Leone, assess its productivity and safety, and estimate its future role in contributing to surgical volume.MethodsThis prospective observational study from a consortium of 16 hospitals evaluated crude in‐hospital mortality over 5 years and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
103
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(107 citation statements)
references
References 38 publications
3
103
0
1
Order By: Relevance
“…This study tested an innovative 36‐month surgical training programme for COs, mainly involving practical in‐service training at district hospitals. The findings of the study suggest that on‐the‐job surgical training of COs is effective, as has been reported elsewhere in Africa. Two follow‐up cohorts of COs have already entered Malawi's national BSc in Surgery programme developed by COST‐Africa.…”
Section: Discussionsupporting
confidence: 69%
“…This study tested an innovative 36‐month surgical training programme for COs, mainly involving practical in‐service training at district hospitals. The findings of the study suggest that on‐the‐job surgical training of COs is effective, as has been reported elsewhere in Africa. Two follow‐up cohorts of COs have already entered Malawi's national BSc in Surgery programme developed by COST‐Africa.…”
Section: Discussionsupporting
confidence: 69%
“…To increase access to emergency obstetric and surgical services, the Sierra Leone Ministry of Health and Sanitation initiated a surgical task‐sharing training programme. ACs are trained to manage basic emergency surgical and obstetric conditions, including surgery such as caesarean section. Community Health Officers and non‐specialist doctors with a minimum of 2 years of work experience can apply for this 2‐year training.…”
Section: Introductionmentioning
confidence: 99%
“…For example, subspecialties included in the definition of surgeon are highly variable, and some databases include trainees or non‐physician providers along with specialists. It was also recognized that using the current Commission definition of this indicator under‐represents the workforce contributing surgical care. For the purposes of comparability and benchmarking, a more uniform definition is needed.…”
Section: Discussionmentioning
confidence: 99%